Determinants of Virological Failure Among HIV-Infected Children on First-Line Antiretroviral Therapy in West Gojjam Zone, Amhara Region, Ethiopia - Shumetie A; Moges NA; Teshome M; Gedif G (HIV/AIDS: Research and Palliative Care, 2021)
Awoke Shumetie,1 Nurilign Abebe Moges,2 Muluken Teshome,2 Getnet Gedif2 1Agut Antiretroviral Treatment Clinic, Agut Health Center, Gish Abay, Amhara Region, Ethiopia; 2Department of Public Health, College of Health Sciences, Debre Markos University, Debre Markos, Amhara Region, EthiopiaCorrespondence: Getnet Gedif P.O.Box: +251269 Tel +251-918-06-66-03Email get4ged@gmail.com; getnet_gedif@dmu.edu.etBackground: Viral load monitoring is a golden indicator for diagnosing treatment failure in patients with HIV. HIV-infected children are considered a priority group for routine viral load monitoring. Globally, the World Health Organization recommends 95% of HIV patients have viral suppression. Factors leading to virological failure are not well understood and studied. This study aimed to determine virological failure among HIV-infected children on first-line antiretroviral therapy in the West Gojjam Zone, Amhara region. Ethiopia.Methods: An institutional-based unmatched case–control study was carried out from October 1 to October 15, 2020, among HIV-infected children on first-line antiretroviral therapy. The study included 94 cases and 276 controls, with a total sample size of 370 out of 378 HIV-infected children. A structured English version checklist was used to collect data through chart review. The data were entered using Epi-data 4.2 and exported into SPSS version 20 for analysis. Descriptive statistics were conducted to summarize the sample characteristics. Bivariate and multivariate analyses were used to describe each explanatory variable’s association with the outcome variable. A bivariate analysis with a p-value < 0.25 was selected for multivariate analysis. Adjusted odds ratio with 95% confidence intervals was conducted, and p-value < 0.05 was considered statistically significant.Results: Non-disclosure (AOR = 4.26; 95% CI: 2.09, 8.70), baseline viral load > 1000 copies/mL (AOR = 10.82; 95% CI: 5.4, 21.67), recent poor adherence (AOR, 6.05, 95% CI, 1.70, 21.55) and missed clinical appointments (AOR = 8.03; 95% CI: 3.88, 16.65) were factors independently associated with virological failure.Conclusion: Disclosure of HIV status of patients early, according to their age and adherence to counseling, should be emphasized. Efforts should be strengthened to trace back for missed clinical appointments and strictly follow-up with antiretroviral (ARV) medication for a baseline viral load > 1000 copies/mL that helps to boost immunity and suppress viral replication.Keywords: HIV/AIDS, ART, case-control, virological failure, children, Amhara region, Ethiopia